2013
DOI: 10.1159/000345964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Placental Protein 13 on the Cardiovascular System in Gravid and Non-Gravid Rodents

Abstract: Objectives: Here, we performed a pathophysiological examination of the vascular function of rodent in the presence of placental protein 13 (PP13) and its implication to regulate the development of preeclampsia. Methods: Single i.v. injection and prolonged in vivo exposure to PP13 via osmotic pumps were performed in gravid and non-gravid rats to examine the influence of PP13 on blood pressure and heart rate in animals. The effect of PP13 was also examined in isolated uterine and mesenteric arteries, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 31 publications
(76 reference statements)
2
38
0
Order By: Relevance
“…The pumps were implanted at gestational day 8 after loading with 127 ng rPP13 (n = 9), the DelT 221 variant (n = 6) or saline (n = 6). As described by Gizurarson et al 2013 [24] the pumps released approximately 0.625 ng PP13/h over 5–7 days (term = day 22).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The pumps were implanted at gestational day 8 after loading with 127 ng rPP13 (n = 9), the DelT 221 variant (n = 6) or saline (n = 6). As described by Gizurarson et al 2013 [24] the pumps released approximately 0.625 ng PP13/h over 5–7 days (term = day 22).…”
Section: Methodsmentioning
confidence: 86%
“…In a recent study, Gizurarson et al 2013 [24] have shown that pregnant rodents exposed to PP13 show a reduced blood pressure. In this paper we wanted to investigate whether beyond the immuno-tolerance impact, the CRD has an additional physiological and morphological impact during pregnancy that is associated with preeclampsia.…”
Section: Introductionmentioning
confidence: 95%
“…The current experiments were designed to extend the findings from a previous pilot study that showed that direct application of PP13 to isolated, pressurized rat uterine arteries elicited arterial vasodilation [30]. There, we also found some preliminary evidence to support a stimulatory effect on arterial remodeling secondary to a single in vivo injection in healthy nonpregnant rats starting late in pregnancy (day 13).…”
Section: Discussionsupporting
confidence: 60%
“…In our previous study [30], we have demonstrated arterial vasodilation and expansion. Here we focused on venous expansion.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation